Illuminance Range for AEB Night Test in Malaysia Based on Selected Road Lights Illuminance Data - M.A.M. Said; S. Mohd; M.B.M. Mokhar; A.S. Ahmad; K.A. Ahmad; T.N.A.T. Kamaruddin; N.A. Husain (Journal of the Society of Automotive Engineers Malaysia, 2024)
The study involves a case study on road lighting in Perak, Malaysia, focusing on Seri Iskandar, Taman Botani, and Meru Impian, to propose a suitable range of illumination for Autonomous Emergency Braking (AEB) night conditions in Malaysia. The selected sites, representing different configurations of two-lane carriageways under Road Type R3, exhibit variations in distances between luminaires and lamp heights. The study underscores the importance of lumen efficacy in LED lighting, explaining its relation to the lifespan of LEDs. The correlation of color temperature (CCT) with human perception is discussed, emphasizing the flexibility of LED lights to adjust CCT based on environmental settings. The Ingress Protection (IP) ratings are introduced to evaluate the resistance of luminaires against dust and liquid intrusion. The methodology involves a reference grid light measurement using EURO NCAP grid calculation at the sites. The lux meter measures illuminance at evenly spaced points between road lights along the x-axis, and uniformity metrics (U_o and U_l) are calculated. Results of lux measurement testing for each site indicate illuminance levels and uniformities variations. The discussion compares these results with Malaysian standards, highlighting potential maintenance issues and environmental factors affecting street lighting performance. The paper concludes by proposing a range for AEB night test illumination based on average values from the sites and literature, considering luminaire duration and road class. The study provides valuable insights into LED road lighting performance in Malaysia and suggests considerations for enhancing standards and testing protocols for AEB night conditions.